Legal Policy of Interfaith Marriage in Indonesia - Hedi, Fathol; Anshori, Abdul Ghofur; Harun, Harun (Faculty of Law, Hasanuddin University, 2017)
Marriage is not just a bond between men and women, but the inner bond between a man and a woman based on the One and Only God. This research was a philosophical normative, thus the approaches used were philosophical, normative, and historical. Besides, a qualitative-descriptive strategy was used in finding a depth description of the law politics of interfaith marriage regulation in Indonesia based on the the 1974 Marriage Law. The results show that the interfaith marriage is not regulated in the 1974 Marriage Law, because: First, the rejection of the majority of Muslims and the faction in Parliament because the interfaith marriage is against the aqidah (matters of faith) of Islam; Second, the interfaith marriage is contrary to the marriage culture in Indonesia, because marriage contains legal, sociology and religious aspects; Third, the interfaith marriage is contrary to the theological teachings of religions in Indonesia that do not want interfaith marriages, such as Islam, Christianity, Protestantism, Hinduism and Buddhism. Furthermore, the interfaith marriage is inconsistent with the philosophical purposes of marriage in Indonesia where the purpose of marriage forms a happy and eternal family based on the One Supreme God.